Revisão taxonômica dos camarões de água doce (Crustacea: Decapoda: Palaemonidae, Sergestidae) da Amazônia Peruana Taxonomic revision of the freshwater shrimps (Crustacea: Decapoda: Palaemonidae, Sergestidae) from the Peruvian Amazonia - Carmen Rosa García-Dávila; Célio Magalhães (Acta Amazonica, 2003)
Foi realizada uma revisão taxonômica das espécies de camarões de água doce da Amazônia peruana que abrangeu oito espécies da família Palaemonidae e uma espécie da família Sergestidae. São descritas duas novas espécies do gênero Pseudopalaemon e feitos os primeiros registros de Euryrhynchus amazoniensis Tiefenbacher, 1978, Macrobrachium jelskii Miers, 1877 e Palaemonetes ivonicus Holthuis, 1950 para o Peru. São fornecidos chave de identificação, dados distribucionais e ilustrações para as espécies estudadas. A taxonomic revision of eight species of freshwater shrimps of the family Palaemonidae and one of the family Sergestidae from the Peruvian Amazonia was made. Two new species of the genus Pseudopalaemon are described, and Euryrhynchus amazoniensis Tiefenbacher, 1978, Macrobrachium jelskii Miers, 1877 e Palaemonetes ivonicus Holthuis, 1950 are recorded from Peru for the first time. Key, distributional data and ilustrations for the species are presented